Adoption of UPI (Unified Payments Interface) by Rural People: An Empirical Investigation (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study is conducted to understand  the adoption of UPI (Unified Payments  Interface) among rural people in India. Meta UTAUT (Unified Theory of Acceptance and  Use of Technology) model is used to evaluate the  critical factors. A well-structured questionnaire  was distributed among 195 users of UPI in  villages of Haryana and the data collected  was analysed using PLS-SEM. A total of 13  hypotheses were proposed and 9 of them were  accepted. Findings show that Social Influence  (SI), Performance Expectancy (PE), Effort  Expectancy (EE), and Facilitating Conditions  (FC) have direct positive influence on Attitude  whereas only PE & FC have direct effect on BI.  Attitude fully mediates the effects of EE & SI on  BI as they do not have direct significant impact  on BI. Whereas, it partially mediates the impact  of FC and PE on BI as they have direct as well as  indirect effect on BI. On the other hand, direct  influence of PE & FC on attitude is strong as  compared to their direct influence on BI. The study explores the critical factors which  influence the adoption of UPI among rural  people and also discusses how this knowledge  can be used to improve UPI adoption among  rural people. UPI has provided newer digital  payment avenue to both urban and rural  consumers in India. However, adoption of UPI  in rural India remains unexplored area. It is one  of the pioneer studies in India context to explore  the adoption of UPI among rural India.
Keywords: Meta-UTAUT; UTAUT; Rural India; UPI; Behavioural Intention; Technology Adoption